The use of Tightrope device as the sole method of fixation in treating lateral end clavicle fractures. (February 2022) - Al-Tawil, K; Garner, M; Antonios, T; Karrupaiah, K; Tahmassebi, R; Colegate-Stone, T; Tavakkolizadeh, A
Background: Lateral end clavicle fractures can be challenging due to the small and often comminuted lateral fragment, problems with union and stability and implant morbidity. We retrospectively reviewed outcomes of Tightrope device in isolation to treat lateral end clavicle fractures. Methods: Subjective and objective measures were assessed for 29 patients. The subjective comprised of functional clinical scores: Oxford shoulder score and EuroQoL5D. The objective measures were maintenance of fracture reduction, bone healing and complications. Results: Median age was 36 years and 72% of cases were male patients. Average clinical follow up time was 21 months. Evaluation of latest radiographs showed that all reductions were maintained post-operatively. Twenty-two fractures had united and one patient had established non-union. Functional outcomes showed predominantly good results with Oxford shoulder score average of 41, EuroQoL5D index score of 0.78 and EuroQol Visual Analogue Scale 76. The overall post-operative complication rate was 10%; only one case requiring a secondary procedure. Discussion: In our series, using the Tightrope as the sole device to treat displaced lateral end of clavicle fractures resulted in good radiological and functional outcomes, with minimal complications requiring secondary procedures. We believe the Tightrope device is a good method of fixing these challenging fractures and advocate its use.